A Comparison of Cooperative Learning Strategies to Traditional Learning Strategies Used on the Same Group of Multicultural Ninth Grade Biology Students during the Same School Year. A Research Paper Regarding a Grant from the Alexandria City School Board Aimed At Improving Existing Programs in This School Division - Kinney, James H. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Much research has been conducted regarding the effectiveness and efficiency of cooperative learning on groups of students. Many student may think they like cooperative learning. Such students, however, may really prefer traditional learning in that same subject if they were taught by the same instructor. Students that have not been taught by the same instructor in that same subject can't accurately determine which method best suits their needs. Therefore, the focus of this study was to give one group of 19 ninth-grade biology students in the Alexandria City, Virginia school district one semester using and promoting only cooperative exercises followed by one semester using and promoting only traditional exercises. The same instructor was used throughout this study. The cooperative learning model consisted of a 3-day cycle of a group quiz, group competition, followed by an individual test. Labs and other activities were also implemented in a cooperative setting. The traditional routine used was teacher lecture, class worksheets, followed by a test. Labs and video presentations were given following the test. An introduction, the methodology, the statistical analysis, and a summary are included. The name of the textbook used in the study, examples of short term and long term achievement tests, and the short term and long term achievement data are appended. (KR)
ERIC Note: Contains some light and broken type which may not produce well. For a related document, see ED 309 096.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Junior High Schools; Science Education; Secondary School Science; Student Attitudes; Teaching Methods; Reports, Research